Profile of the elementary school principal in the divisions of Leyte I and Leyte II - Rosillo, Carlos T.
The purpose of the study is to determine the profile of the elementary school principal in the divisions of Leyte I and Leyte II. Findings of the study suggest criteria for recruitment, selection and appointment of elementary school principals and may provide guidelines for the evaluation of the present crop of elementary school principals.